(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study examines the influence of social media on the purchasing decisions of Generation Z regarding organic cosmetic products. Gen Z, a digitally native and socially conscious group, relies significantly on platforms like Instagram, YouTube, and Facebook to engage with beauty-related content, find new products, and validate buying decisions via reviews and influencer endorsements. The study uses a quantitative research design, collecting primary data from roughly 60 Gen Z respondents via a structured questionnaire with multiple-choice and Likert scale items. The data was examined using descriptive statistics, frequency distributions, and correlation analysis. The study found that Gen Z consumers have a high level of environmental and health awareness, with an average awareness score of 4.2 on a five-point scale. Trust in online reviews showed a large positive connection (r = +0.65) with purchasing intent, demonstrating that reliable web information had a major impact on their purchasing behaviour. Influencer posts were the most effective sort of material, followed by detailed product reviews. Traditional commercials and lectures proved to be less compelling. Overall, the survey emphasizes the relevance of original, relatable, and trustworthy online content in influencing Gen Z consumer choices. These insights provide useful information for brands looking to connect with this environmentally conscious and media-savvy generation.